Ozone therapy on Otorhinolaryngology. A five-year study. - Armando Figueroa Hernández; Juan M. Salomón Bacallao; Alejandro Díaz González (Medisur)
Fundament: The ample active spectre of ozone in medicine is based in a series of properties that positively influence certain metabolic processes, whose alterations are cause for many diseases. Methods: Prospective-descriptive study about the treatment with ozone, besides the conventional therapeutics, to patients bearing affections of possible vascular ethiology as acufenos, peripheral vertiginous syndrome, sudden hypacusia, and others of infectious origin as recurrent suppurated half chronic otitis, rebel to conventional therapeutics. Tran rectal bias was used during three weeks, the results and evolution of patients were controlled. Results: ozone treatment effectiveness was proved (91%), with no intoxication or intolerance, a rapid remission of vertigo was observed in nearly all patients since first sessions, and evident betterment or remission of acufenos and the hypacusia.